Discovery of a Collimated Jet from the Low-luminosity Protostar IRAS 16253−2429 in a Quiescent Accretion Phase with the JWST - Mayank Narang; P. Manoj; Himanshu Tyagi; Dan M. Watson; S. Thomas Megeath; Samuel Federman; Adam E. Rubinstein; Robert Gutermuth; Alessio Caratti o Garatti; Henrik Beuther; Tyler L. Bourke; Ewine F. Van Dishoeck; et al. (The Astrophysical Journal Letters, 2024)
Investigating Protostellar Accretion (IPA) is a JWST Cycle 1 GO program that uses NIRSpec integral field units and MIRI Medium Resolution Spectrograph to obtain 2.9–28 μ m spectral cubes of young, deeply embedded protostars with luminosities of 0.2–10,000 L _⊙ and central masses of 0.15–12 M _⊙ . In this Letter, we report the discovery of a highly collimated atomic jet from the Class 0 protostar IRAS 16253−2429, the lowest-luminosity source ( L _bol = 0.2 L _⊙ ) in the IPA program. The collimated jet is detected in multiple [Fe ii ] lines and [Ne ii ], [Ni ii ], and H i lines but not in molecular emission. The atomic jet has a velocity of about 169 ± 15 km s ^−1 , after correcting for inclination. The width of the jet increases with distance from the central protostar from 23 to 60 au, corresponding to an opening angle of 2.°6 ± 0.°5. By comparing the measured flux ratios of various fine-structure lines to those predicted by simple shock models, we derive a shock speed of 54 km s ^−1 and a preshock density of 2.0 × 10 ^3 cm ^−3 at the base of the jet. From these quantities and using a suite of jet models and extinction laws, we compute a mass-loss rate between 0.4 and 1.1 ×10 ^−10 M _⊙ yr ^−1 . The low mass-loss rate is consistent with simultaneous measurements of low mass accretion rate (2.4 ± 0.8 × 10 ^−9 M _⊙ yr ^−1 ) for IRAS 16253−2429 from JWST observations, indicating that the protostar is in a quiescent accretion phase. Our results demonstrate that very low-mass protostars can drive highly collimated, atomic jets, even during the quiescent phase.